Deoxynivalenol Induces Caspase-8-Mediated Apoptosis through the Mitochondrial Pathway in Hippocampal Nerve Cells of Piglet - Li Cao (Toxins, 2021)
Deoxynivalenol (DON) is a common trichothecene mycotoxin found worldwide. DON has broad toxicity towards animals and humans. However, the mechanism of DON-induced neurotoxicity in vitro has not been fully understood. This study investigated the hypothesis that DON toxicity in neurons occurs via the mitochondrial apoptotic pathway. Using piglet hippocampal nerve cells (PHNCs), we evaluated the effects of different concentrations of DON on typical indicators of apoptosis. The obtained results demonstrated that DON treatment inhibited PHNC proliferation and led to morphological, biochemical, and transcriptional changes consistent with apoptosis, including decreased mitochondrial membrane potential, mitochondrial release of cytochrome C (CYCS) and apoptosis inducing factor (AIF), and increased abundance of active cleaved-caspase-9 and cleaved-caspase-3. Increasing concentrations of DON led to decreased B-cell lymphoma-2 (Bcl-2) expression and increased expression of BCL2-associated X (Bax) and B-cell lymphoma-2 homology 3 interacting domain death agonist (Bid), which in turn increased transcriptional activity of the transcription factors AIF and P53 (a tumor suppressor gene, promotes apoptosis). The addition of a caspase-8 inhibitor abrogated these effects. These results reveal that DON induces apoptosis in PHNCs via the mitochondrial apoptosis pathway, and caspase-8 is shown to play an important role during apoptosis regulation.